2010
DOI: 10.2217/pgs.10.54
|View full text |Cite
|
Sign up to set email alerts
|

HLA-B*5901 is Strongly Associated with Methazolamide-Induced Stevens–Johnson Syndrome/Toxic Epidermal Necrolysis

Abstract: A strong association was observed between HLA-B*5901 and methazolamide-induced SJS/TEN in Korean patients. HLA-B*5901 may be a useful screening marker for predicting methazolamide-induced SJS/TEN in patients of Korean and Japanese ancestry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(57 citation statements)
references
References 25 publications
4
51
2
Order By: Relevance
“…These include HLA-B*13:01 with dapsone [33], HLA-A*31:01, and HLA-B*15:11 with CBZ [28,29,34,35], HLA-B*15:02 with phenytoin [23,36], HLA-B*57:01 with abacavir [37], HLA-B*38 with sulfamethoxazole or lamotrigine [32], HLA-B*73 with oxicam [32], and HLA-B*59:01 with methazolamide [38]. A summary of genetic relationships between various HLA allotypes and drug-mediated SCARs is shown in Table 1.…”
Section: Genetic Susceptibility To Scarsmentioning
confidence: 99%
“…These include HLA-B*13:01 with dapsone [33], HLA-A*31:01, and HLA-B*15:11 with CBZ [28,29,34,35], HLA-B*15:02 with phenytoin [23,36], HLA-B*57:01 with abacavir [37], HLA-B*38 with sulfamethoxazole or lamotrigine [32], HLA-B*73 with oxicam [32], and HLA-B*59:01 with methazolamide [38]. A summary of genetic relationships between various HLA allotypes and drug-mediated SCARs is shown in Table 1.…”
Section: Genetic Susceptibility To Scarsmentioning
confidence: 99%
“…SJS/TEN is now considered to be an autoimmune disease and some studies showed the strong correlation with methazolamide–induced SJS/TEN and HLA-B59 serotype that is often seen in East Asians [9, 43-45]. On the other hand, P450 is reported to the major target of the patients of autoimmune hepatitis, some of which related with certain HLA serotypes [46].…”
Section: Discussionmentioning
confidence: 99%
“…There are cases where a specific immune response to a drug can Pharmacogenomics (2012) 13(11) [72] A*3101 Japanese, northern European, Korean [58][59][60][61] Oxcarbazepine Han Chinese [48,64,140] Sulfamethoxazole B*38 European [104] Methazolamide B*5901, Cw*0102 alleles and B*5901-Cw*0102-A*2402 haplotype Korean and Japanese [142] Sulphonamides A*29, B*12 and DR7 European [143] Oxicam B*73 European [104] A*2 and B*12 European [143] Caucasians [146] A*3101 Northern European, Japanese, Korean [58][59][60][61] A*11 and B*51 (weak) Japanese [58] Delayed rash (nonsystemic)…”
Section: Models For Drug-induced Hypersensitivity Reactionsmentioning
confidence: 99%